Elucidation of the evolutionary history of Stipa in China using comparative transcriptomic analysis - Sha, Na; Li, Zhiyong; Sun, Qiang; Han, Ying; Tian, Li; Wu, Yantao; Li, Xing; Shi, Yabo; Zhang, Jinghui; Peng, Jiangtao; Wang, Lixin; Dang, Zhenhua; et al. (Frontiers in Plant Science, 2023)
Phylogenetic analysis provides crucial insights into the evolutionary relationships and diversification patterns within specific taxonomic groups. In this study, we aimed to identify the phylogenetic relationships and explore the evolutionary history of Stipa using transcriptomic data. Samples of 12 Stipa species were collected from the Qinghai-Tibet Plateau and Mongolian Plateau, where they are widely distributed, and transcriptome sequencing was performed using their fresh spikelet tissues. Using bidirectional best BLAST analysis, we identified two sets of one-to-one orthologous genes shared between Brachypodium distachyon and the 12 Stipa species (9397 and 2300 sequences, respectively), as well as 62 single-copy orthologous genes. Concatenation methods were used to construct a robust phylogenetic tree for Stipa, and molecular dating was used to estimate divergence times. Our results indicated that Stipa originated during the Pliocene. In approximately 0.8 million years, it diverged into two major clades each consisting of native species from the Mongolian Plateau and the Qinghai-Tibet Plateau, respectively. The evolution of Stipa was closely associated with the development of northern grassland landscapes. Important external factors such as global cooling during the Pleistocene, changes in monsoonal circulation, and tectonic movements contributed to the diversification of Stipa. This study provided a highly supported phylogenetic framework for understanding the evolution of the Stipa genus in China and insights into its diversification patterns.